Oncologic Imaging: Urology - Kim, Seung Hyup; Cho, Jeong Yeon (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is designed as a reference and working guide for practitioners who deal with patients with neoplastic diseases of the urinary tract and male genitalia, including tumors of the kidney, ureter and urinary bladder, prostate, testis, adrenal gland, and retroperitoneum. Each chapter describes and illustrates key imaging findings relevant to the characterization, differential diagnosis, and staging of lesions. Pattern recognition is facilitated through the use of schematic drawings, and imaging findings on post-treatment follow-up also form an important component of the book. Brief core descriptions of related multidisciplinary fields, such as nuclear medicine, pathology, urologic surgery, and radiation oncology, are included whenever relevant. .